Adaptations to scale-up an early childhood education and care physical activity intervention for real-world availability - Play Active - Matthew Mclaughlin; Andrea Nathan; Ashleigh Thornton; Jasper Schipperijn; Stewart G. Trost; Hayley Christian (BMC, 2023)
Abstract Background Adaptations for scale-up are ubiquitous but are rarely described in detail. Adaptations may be a key reason for the "scale-up penalty" which is when there is a reduction in intervention effect size following scale-up. The Play Active intervention consists of a physical activity policy for early childhood education and care (ECEC) services, with accompanying implementation support strategies. It was first implemented with 81 ECEC services in Perth, Western Australia, in 2021 - with significant positive changes in physical activity practice uptake. The aim of this paper is to describe the extent, type, fidelity consistency, goals, size, scope, and proposed impact of proposed adaptations to the implementation support strategies for scaling-up Play Active. Methods Proposed adaptations were defined as planned changes, made prior to making the intervention available. The authors created a list of adaptations from a comparison of the Play Active implementation support strategies, before and after adaptation for proposed statewide availability across Western Australia, Queensland and South Australia, Australia. We used the Framework for Reporting Adaptations and Modifications-Enhanced Implementation Strategies (FRAME-IS) to code adaptations to implementation support strategies. Three authors coded each adaptation and rated their size, scope and proposed impact. Results Fifty-three adaptations to Play Active were identified. Most (68%) were proposed for the 'content' of implementation strategies, including aspects of their delivery. In practice, this involved changing the delivery mode of implementation support strategies from phone call and email support, to website-based delivery. More than half (56%) of adaptations involved 'adding elements' for scale-up. Most adaptations were 'fidelity consistent' (95%). The main goals for adaptations were related to 'increasing the acceptability, appropriateness, or feasibility' (45%), 'decreasing the costs' (19%) and 'increasing adoption of the evidence-based practice' (19%). Adaptations were small to medium in size, with most proposed to have a positive (87%) or neutral (8%) effect on the effectiveness of the intervention, rather than negative (4%). Conclusions A large number of small, fidelity-consistent, adaptations were proposed for Play Active scale-up. Overall, the process of reporting adaptations was found to be feasible. To understand the impact of these adaptations, it will be important to re-evaluate implementation, effectiveness and process outcomes, at-scale.